(untitled) (Journal of Informatics Education and Research, 2025)
The financial indZustry has undergone significant transformations over the past few decades, particularly within risk management professions. This paper examines how Operational Risk Management (ORM) compares with other risk management domains, namely Compliance and Internal Audit, within the top 20 global investment banks. By analyzing key criteria such as Salary and Compensation, Professional Growth, Technology Usage, Regulatory Influence, and Job Market Demand, the study offers a comprehensive understanding of the similarities and differences between these professions. The findings reveal unique aspects of each domain, providing actionable insights for practitioners and organizations to make informed decisions regarding career paths and organizational structures. Additionally, the paper explores the impact of technological advancements and regulatory changes on these professions, highlighting the evolving landscape of risk management in the financial sector.